Implementasi Undang-Undang Nomor 24 Tahun 2011 Tentang Badan Penyelenggaraan Jaminan Sosial pada PT. Horiko Abadi Kabupaten Buleleng - Gede Oscar Geovani; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Jurnal Konstruksi Hukum, 2020)
Social security provides protection for workers in the socio-economic risks that befall workers in carrying out their work in the form of work accidents, illness, old age, or death. This thesis discusses the implementation of Law Number 24 of 2011 concerning the Social Security Administration at PT. Horiko Abadi, Buleleng Regency. Based on the description above, this study aims to determine the application of Law Number 24 of 2011 concerning the Social Security Administration at PT. Horiko Abadi, Buleleng Regency 2 legal sanctions against the company in the event of a violation of the provisions of the social security program. The research method used is the empirical juridical method. The location of this research was conducted at PT. Horiko Abadi, Buleleng Regency, a company engaged in the breeding of shellfish and pearl cultivation. Based on the research results, PT. Horiko Abadi has implemented social security protection for all permanent employees in the company in accordance with the provisions of Law Number 24 of 2011 concerning Social Security Administering Bodies, and sanctions for companies that have not implemented the provisions of Law Number 24 of 2011 Regarding the Social Security Administering Body, it is still in the guidance or warning stage until the company concerned can carry out the provisions of the legislation.